EFEKTIVITAS PERATURAN PEMERINTAH NO. 43 TAHUN 2014 TENTANG DESA TERHADAP TINGGINYA KASUS KORUPSI DANA DESA PERSFEKTIF FIQH SIYASAH - Natasyah, Indah Nurhazlin; Pasaribu, Ilhamsyah (Universitas Ekasakti, 2023)
Based on data from Indonesia Corruption Watch (ICW), the village budget is the most vulnerable to corruption. In the last seven years, there have been 592 cases of corruption, and ICW noted that the village government was the institution that carried out the biggest corruption cases. This research uses a type of normative juridical research that refers to statutory law, namely PP No. 43 of 2014 concerning implementing regulations for the Village Law and other literature as a support for literacy with the aim of knowing the effectiveness of these regulations for the high number of village fund corruption cases in Indonesia and their studies according to fiqh siyasah. The results of this study indicate that PP No. 43 of 2014 when analyzed based on a juridical approach, namely Law no. 12 of 2011 concerning the procedure for forming laws and regulations, there are elements that do not work effectively in society, namely elements of usability and efficiency, PP No. 43 of 2014 does not clearly provide oversight over the use of Village Funds by the village government, it should be as implementing regulations of the Village Law PP No. 43 of 2014 provides effective efficiency, especially in limiting cases of village fund corruption in Indonesia.